Microscopic characteristics and corrosion rate modeling in galvanized high-strength steel wires - Haiping Zhang; Haojie Liu; Fanghuai Chen; Yuan Luo; Xinhui Xiao; Yang Deng; Naiwei Lu; Yang Liu (Journal of Materials Research and Technology)
The electrochemical reaction mechanism of galvanized high-strength steel wires (GHSSWs) has not been fully elucidated. Scholars have observed a significant discrepancy between the theoretical mass loss rate calculated using the Faraday equation for electrochemical corrosion and the experimental values. To address this issue, this study conducted electrochemical corrosion tests on 195 sets of GHSSWs. Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and non-contact 3D scanning systems were used to characterize the surface morphology and elemental composition of specimens before and after rust removal, revealing the reaction mechanism during electrochemical corrosion in GHSSWs. The correlation between corrosion length, current intensity, and electrolysis time with the corrosion rate was investigated, and a correction function for mass loss in GHSSWs under constant current electrochemical corrosion was established. The results indicate that during the initial stage of electrochemical corrosion in GHSSWs, internal stress between the corrosion products and the GHSSWs substrate leads to the formation of apparent cracks in the corroded wire, increasing the contact area between the specimen and the electrolyte and accelerating the corrosion process. In later stages, the formation of needle-like α-FeOOH corrosion products provides protective effects, leading to a decrease in the corrosion rate.